Role of the Pectoralis Major Muscle Flap in the Multidisciplinary Treatment of Esophageal Cancer - Lauren Barter, BSc; David Forner, MD, MSc; Daniel G. French, MD, MASc; Alexander Ednie, MD; Gail E. Darling, MD; Matthew H. Rigby, MD, MPH (Plastic and Reconstructive Surgery, Global Open)
Background:. Management of esophageal cancer is complex. Esophagectomy is associated with risk of significant complications. In this case series, we share the experience of our multidisciplinary team of thoracic surgeons and otolaryngologists in managing complications arising in the surgical treatment of esophageal cancer with the assistance of regional tissue transfer in the form of the pectoralis major flap. Methods:. We present a case series highlighting 3 patients who underwent esophagectomy who experienced significant anastomotic or conduit complications which were managed with a pectoralis muscle flap. Results:. Complications included tracheoesophageal fistula, refractory stenosis, and gastric conduit necrosis. Using a pectoralis major muscle flap with both myocutaneous and myofascial transfers was key to successful management. In the first patient, esophageal stent erosion after posterior tracheal wall dissection resulted in a tracheoesophageal fistula reconstructed through interposition of a myofascial flap. In the second patient, a tubed myocutaneous flap was interposed between the remnant gastric conduit and cervical esophagus to manage a posttreatment stenosis following resection of the stenosed segment. Finally, a myofascial flap was utilized to bolster a colonic interposition flap after initial necrosis of a gastric conduit that necessitated the creation of a temporary pharyngocutaneous fistula and subsequent colon interposition. Conclusions:. Multidisciplinary care and collaboration are integral components for optimization of patient outcomes. In this case series, otolaryngology and thoracic surgery utilized multiple tools within their armamentarium to manage complications associated with the surgical management of esophageal cancer.